(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2019)
The succession of Pragian to Emsian (Early Devonian) brachiopod faunas from the Rhenish Massif (Germany) is briefly reviewed and interpreted with reference to a changing palaeoenvironment. A series of bioevents caused partial extinction or emigration of brachiopod species and succeeding immigration and dispersal of new species and speciation. The interplay of sea-level fluctuations, subsidence history and siliciclastic input from the Old Red Continent triggered the specific suitability of potential brachiopod habitats on the Rhenish Shelf. Three new taxa are proposed: Fascistropheodonta? wiltzensis n. sp., Ingentistrophia gen. n. and Pachyschizophoria amygdalina n. sp.